Improve Service of The Digital Platform Using Value Co-Creation to Optimize Digital Transformation Process of Non-Profit Organization In Indonesia (Case: XYZ Foundation) - Fakhruddin, Muhammad Rifqi; Novani, Santi (Cv. Syntax Corporation Indonesia, 2023)
In the competitive landscape today for Non-profit Organizations (NPO), transformation is necessary, especially for mature NPO organizations. Digital transformation is the process of organizations to improve radically their performance using technology. The output from digital transformation is a digital platform as a new business model or core of the digitalization business process. One way for an organization to build a new business model is using co-creation, which means creating process value-making with the customer as the main collaborator. this research will overview a potential implementation of value co-creation in the NPO digital platform and the impact on the digital transformation process. The impact will be orchestrated with a mechanism in a digitally transformed innovation process. This research uses mixed methods qualitative & quantitative from key stakeholders in the NPO and donors of the NPO. The finding: transparency is the key for NPO to recover their current condition and it can implement in digital platforms. Opening three processes of transparency (distribution preparation -distribution process - report) and can also show their area distribution. But the process must be orchestrated with internal stakeholders related to digital adoption, leveraging digital technologies, developing digital capabilities, and managing boundaries. There are several recommendation plans that can implement in Digital Transformation Process XYZ for continuous improvement.